Microglia in Alzheimer's Disease. (14th August 2014) - Li, Ying; Tan, Meng-Shan; Jiang, Teng; Tan, Lan
Abstract : Alzheimer's disease (AD) is a familiar neurodegenerative disease in the elderly. In this paper, we will review current viewpoints of microglial activation, inflammatory regulatory systems, and their relationship with AD pathology and etiology. Microglia cells are macrophage and representative of the innate immune system in brain. AD brain is marked by obvious inflammatory features, in which microglial activation is the driving force. β -amyloid protein sedimentation activates microglia cells, which causes the inflammation in AD. Microglia cells have dual roles: they provoke the release of inflammatory factors and cytotoxins leading to neuronal injuries and death; on the other hand, they have the neuroprotective effects. Through this, we hope to illustrate that the anti-inflammatory defenses of neurons can be practiced in the future strategy for recuperating the balance between the levels of inflammatory mediators and immune regulators in AD.